Hukum Islam di Indonesia : perspektif Muhammadiyah dan NU - Ka'bah, Rifyal, 1950- (Jakarta : Universitas Yarsi, 1999)
Islamic law in Indonesia from Muhammadiyah and N.U. perspectives.
Revision of the author's thesis (doctoral--Universitas Indonesia, 1998).
Includes bibliographical references (p. [273]-291) and index.
Keywords: Civil law -- Indonesia; Islamic law -- Indonesia